Household Food Items Toxic to Dogs and Cats - Cortinovis, Cristina; Caloni, Francesca (Frontiers in Veterinary Science, 2016)
Several foods that are perfectly suitable for human consumption can be toxic to dogs and cats. Food-associated poisoning cases involving the accidental ingestion of chocolate and chocolate-based products, Allium spp. (onion, garlic, leek and chives), macadamia nuts, Vitis vinifera fruits (grapes, raisins, sultanas and currants), products sweetened with xylitol, alcoholic beverages and unbaked bread dough have been reported worldwide in the last decade. The poisoning episodes are generally due to lack of public knowledge of the serious health threat to dogs and cats that can be posed by these products. The present review aims to outline the current knowledge of common food items frequently involved in the poisoning of small animals, particularly dogs, and provides an overview of poisoning episodes reported in the literature.